LncRNA RP11-818O24.3 regulates proliferation and differentiation of hair follicle stem cells by targeting FGF2/PI3K/AKT pathway - Linlin Bao; Haibo Zhao; Haiyue Ren; Chong Wang; Su Fang (PLoS ONE, 2025)
Hair follicle stem cells (HFSCs) play critical roles in adult hair regeneration, owing to its self-renewal and multipotent differentiation properties. Emerging evidence has shown that long noncoding RNAs (LncRNAs) are implicated in biological processes such as proliferation, differentiation and apoptosis. However, the specific role of LncRNA RP11-818O24.3 in regulating HFSCs remains unclear. To explore the effect of LncRNA RP11-818O24.3 on HFSCs, stable LncRNA RP11-818O24.3 overexpression and knockdown HFSCs were established using a lentivirus vector system. The effect of LncRNA RP11-818O24.3 on proliferation was evaluated by Cell Counting Kit-8 (CCK8) and EdU incorporation experiments. The differentiation of HFSCs into neurons and keratinocyte stem cells was detected by immunofluorescence staining. We showed that LncRNA RP11-818O24.3 overexpression promoted the proliferation and inhibited cell apoptosis in HFSCs. High levels of LncRNA RP11-818O24.3 promoted the differentiation of HFSCs into CD34+K15+ keratinocyte progenitors and CD34+Nestin+neuron-specific enolase (NSE)+ neural stem cells. Additionally, LncRNA RP11-818O24.3 increased fibroblast growth factor 2 (FGF2) expression and the subsequent activation of the PI3K/AKT signaling pathway. These data demonstrated that LncRNA RP11-818O24.3 promotes self-renewal, differentiation, and the capability to inhibit apoptosis of HFSCs via FGF2 mediated PI3K/AKT signaling pathway, highlighting its potential role as a therapeutic strategy for treating hair loss diseases.